Frequency and direction of competitive anger in contact sports - Robazza, B.; Bertollo, M.; Bortoli, L. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of the present study was to investigate whether athletes involved in physical contact sports may interpret their feelings of anger as facilitative of performance, and to examine differences in the interpretation of anger as a function of the type of sport (team vs individual) or the competitive skill level (high vs low). Methods: A modified version of the State-Trait Anger Expression Inventory was administered to 100 Italian adult male athletes practicing rugby or individual combat sports (judo, freestyle wrestling, or Greco-Roman wrestling). The questionnaire was intended to measure the frequency and the direction (i.e., the facilitative-debilitative interpretation) of competitive anger. Results: Many athletes engaged in contact sports tended to interpret their competitive anger as facilitative of performance rather than debilitative. The type of sport and the athlete's standard level can mediate the individual's interpretation of the effects of anger symptoms upon performance. Conclusions: Competitors can interpret their anger as helpful to energize behavior and channel physical and mental resources for skill execution. Practitioners should assist athletes in gaining control over anger rather than attempting to suppress it.